Postnatal Amelioration of Fetal Right Ventricular Hypoplasia Associated with Large Eustachian Valve: A Case Report - Iwatani, Ayaka; Miyake, Fumihito; Ishido, Hirotaka; Kanai, Masayo; Ishiguro, Akio; Iwamoto, Yoichi; Kabe, Kazuhiko; Masutani, Satoshi (American Journal of Perinatology Reports, 2019)
In fetuses, the Eustachian valve directs oxygenated blood returning from the inferior vena cava into the left atrium via the foramen ovale. If too large, the Eustachian valve can restrict right ventricular inflow, as well as induce postnatal cyanosis via an interatrial right-to-left shunt. We report a fetal case of postnatal amelioration of the tricuspid valve and right ventricle hypoplasia, despite significant right ventricular hypoplasia associated with a large Eustachian valve. Application of an appropriate respiratory management regimen to help reduce pulmonary vascular resistance is of particular importance for the reversal of the right-to-left shunt via the foramen ovale and associated increases in right ventricular inflow.
Keywords: tricuspid; Eustachian valve; right ventricle; hypoplasia; fetal; foramen ovale